Pengaruh Profitabilitas, Ukuran Perusahaan, dan Leverage Terhadap Tax Avoidance Pada Perusahaan Farmasi yang Terdaftar Di Bursa Efek Indonesia Tahun 2010-2018 - Ari Prabowo (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2020)
This study aims to examine the effect of company characteristics, namely: profitability, company size and asset growth on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange from 2013 to 2017, with family ownership as a moderating variable. This research uses descriptive statistical research with a quantitative approach which is measured using panel data regression analysis. To estimate the model coefficients in the panel data, the Eviews 10 program was used. The population of this study were manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2013 to 2017. The sample was determined based on the purposive sampling method, with a total sample of 25 companies. manufacturing so that the total observations in this study were 125 observations. The data used in this research is secondary data. The data collection technique used the documentation method through the official IDX website: www.idx.co.id and the official website of each company that was used as the research sample. The results of the study prove that (1) Profitability has a negative but not significant effect on capital structure. (2) Firm size has a significant positive effect on capital structure. (3) Asset growth has a negative but not significant effect on capital structure. (4) Family ownership does not moderate the effect of profitability on capital structure. (5) Family ownership moderates the effect of firm size on capital structure. (6) Family ownership does not moderate the effect of asset growth on capital structure.